ADVANCED PEDAGOGICAL TECHNOLOGIES IN ENGLISH CLASSES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In this article, the methods of classification of innovations in English language classes are covered, it mentions modern methods.